Bagaimana Service Recovery Mempengaruhi Loyalitas Konsumen? - Carla Elisabeth Stephanie; Rita Komaladewi; M Aqshel Revinzky (Valid: Jurnal Ilmiah, 2020)
Based on a survey from Jakpat, 40.96% of online transportation users in Indonesia use Gojek and Grab together, this phenomenon is a problem for all of these companies. This kind of customer behavior is caused by several factors, one of which is customer disappointment with some services. Service recovery is one way for companies to overcome or correct customer disappointment arising from service failures. Service recovery is done so that customers do not have a bad impression of the company that can result in trauma or negative word-of-mouth. This study aims to determine the impact or influence of three factors that affect service recovery, namely distributive justice, interactional justice and procedural justice carried out by digital transportation companies in Indonesia, namely Gojek on customer loyalty. The method used in this research is descriptive and verification. The survey was used in this study as a tool to get 104 research respondents who had complained about the services provided by Gojek. Survey data were analyzed using Structure Equation Model (SEM) with Partial Least Square (PLS) method. The t-statistics test was also used in this study to test the existing hypotheses. The results of data processing in this study indicate that the three factors of service recovery, namely distributive justice, interactional justice and procedural justice, have a weak / no significant effect on consumer loyalty. And distributive justice is the most dominant factor in influencing Gojek consumer loyalty. However, if carried out simultaneously or together, these three factors provide a moderate or moderately influential effect on consumer loyalty